Heterosis of Linear Body Traits in Crossbred Cattle Reared in the Humid Rainforest Zone of Nigeria - Inyang, E.C; Nwachukwu, E.N; Ogbu, C.C.; Kalla, D.J.U.; Ukwu, H.O.; Ezea, J. (Nigerian Journal of Animal Science, 2026)
This study evaluated the heterosis of linear body traits at various growth phases in F1 crossbred cattle namely BOxND, BOxWF, GUxWF, NDxMU, NDxWF, and WFxMU relative to the average of purebred generation. Muturu (MU) and N’dama (ND) were the reference breeds in the crossbreeding programme. 1,724 linear body trait data (sexes combined) at weaning, yearling, grower, and adult stages were analyzed. Significantly (P < 0.000) higher linear body trait values were observed in Sokoto Gudali (GU), and Red Bororo (BO) compared to MU, ND, and White Fulani (WF) across the growth phases while GUxWF and BOxWF were superior (P < 0.000) to other hybrids. Mean heterosis were non-significant (P>0.05) but positive (except at grower phase) for HL; positive but significant only at weaning for BL; positive but significant only at yearling and grower phases for CG; and positive but significant at weaning, yearling, and grower phases for HW. Heterosis relative to the better parent in each cross were essentially negative, but generally positive relative to the inferior parent. Heterosis relative to the mean of parental breeds at weaning, yearling, grower, and adult phases was 2.54, 2.66, - 0.67, and 3.58 %, respectively for HL; 5.70, 9.08, 8.06, and 3.61 %, respectively for BL; 1.86, 5.40, 0.18, and 1.36 %, respectively for CG; and 7.57, 5.46, 5.76, and 3.88 %, respectively for HW. In conclusion, crossbreeding can be used to improve the growth and linear body traits of trypanotolerant ND, and MU cattle breeds.